3D printed bone tissue regenerative PLA/HA scaffolds with comprehensive performance optimizations. (March 2021) - Zhang, Boqing; Wang, Ling; Song, Ping; Pei, Xuan; Sun, Huan; Wu, Lina; Zhou, Changchun; Wang, Kefeng; Fan, Yujiang; Zhang, Xingdong
Abstract: Polylactic acid/Hydroxyapatite (PLA/HA) composite was widely studied and applied in the field of biomaterials for its good processability, bioactivity, and mechanical properties. In addition to traditional preparation methods, additive manufacturing has also been adopted to prepare PLA/HA composites with customized geometries. This work combined the comprehensive optimized PLLA (L-polylactic acid)/nano-HA (nHA) composite with the low-cost and stable Fused deposition modeling (FDM) technology to successfully prepare PLLA/nHA porous bone repair scaffolds. The results showed that PLLA/nHA composite ink satisfied the smoothness of printing, and the accuracy also met the requirements of personalized bone repair application. The high loaded nHA scaffold had suitable compressive strength was significantly higher than those of pure HA ceramic scaffold and cancellous bone. Besides, in vitro bone-like apatite formation on the surface in the degradation process and in vivo evaluations further verified its good osteogenic property. Compared with other complex and cutting-edge 3D printing technologies, this study provides a low-cost, stable, simple and fast way to realize personalized printing of bone repair scaffolds, which is undoubtedly conductive to the improvement and rapid deployment of personalized biomaterials in clinical applications. Graphical abstract: Unlabelled Image Highlights: Comprehensive optimized PLLA/nano-hydroxyapatite composite was made successfully for bone repair scaffold printing. Bone-like apatite can form on the scaffold surface in vitro degradation experiments just in PBS, indicating the high bioactivity of scaffold. The high loaded nano- hydroxyapatite scaffold has suitable compressive strength and good osteogenic property. This study provides a low-cost, stable, simple and fast way to realize personalized printing of bone repair scaffolds.